2012
DOI: 10.1037/a0028949
|View full text |Cite
|
Sign up to set email alerts
|

Callings and work engagement: Moderated mediation model of work meaningfulness, occupational identity, and occupational self-efficacy.

Abstract: This is an unedited manuscript published in the Journal of Counseling PsychologyPlease note that the published underwent minor additional editing in style and content.Cite as: Hirschi, A. (2012) The funding source had no involvement in study design, in the collection, analysis and interpretation of data, in the writing of the report, or in the decision to submit the article for publication. CALLING AND WORK ENGAGMENT Callings and Work Engagement: Moderated Mediation Model of WorkMeaningfulness, Occupational Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
285
1
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(321 citation statements)
references
References 56 publications
14
285
1
21
Order By: Relevance
“…Therefore, if ability is strengthened through behavioural involvement in an occupation, it could play a role in shaping the appraisal of one's work as a calling (Dobrow, 2013). While it has been suggested that the presence of a calling can increase an individual's belief in one's ability (Hirschi, 2012), the findings of the present study suggest that a loss of self-efficacy within a work domain can alter one's occupational outlook (Bandura, Barbaranelli, Caprara, & Pastorelli, 2001). One's expectations and efficacy beliefs can therefore not only help explain how initial callings develop or are subject to erosion over time, but also assist in clarifying how positive and supportive working environments are necessary for the growth and sustenance of a calling (Duffy, Manuel, Borges, & Bott, 2011).…”
Section: Calling Orientations: India 23contrasting
confidence: 47%
“…Therefore, if ability is strengthened through behavioural involvement in an occupation, it could play a role in shaping the appraisal of one's work as a calling (Dobrow, 2013). While it has been suggested that the presence of a calling can increase an individual's belief in one's ability (Hirschi, 2012), the findings of the present study suggest that a loss of self-efficacy within a work domain can alter one's occupational outlook (Bandura, Barbaranelli, Caprara, & Pastorelli, 2001). One's expectations and efficacy beliefs can therefore not only help explain how initial callings develop or are subject to erosion over time, but also assist in clarifying how positive and supportive working environments are necessary for the growth and sustenance of a calling (Duffy, Manuel, Borges, & Bott, 2011).…”
Section: Calling Orientations: India 23contrasting
confidence: 47%
“…Hirschi (2012) discovered that people reported more stress and reduced job satisfaction when they did not feel like they were fulfilling their purpose. Conversely, fulfilling one's career calling may serve as a moderator against stress.…”
Section: Definitions Of Stress Related Prevention Strategies and Promentioning
confidence: 99%
“…In Europe, the engagement construct has emerged mainly in professional and occupational activities, and has been researched primarily in relation to business organizations (Bakker et al 2008;Hirschi 2012;Schaufeli & Bakker 2010). From the business organizations' perspective, work engagement has been defined as a positive, fulfilling, affective-motivational psychological state that is characterized by vigour, dedication and absorption associated with work-related well-being (Bakker et al 2008).…”
Section: Introductionmentioning
confidence: 99%